2018
DOI: 10.1002/jum.14700
|View full text |Cite
|
Sign up to set email alerts
|

Current Experience of Ultrasound Training in Otolaryngology Residency Programs

Abstract: Although current experience is variable, there is a strong interest in increasing resident skill acquisition in ultrasound training among otolaryngology residents. Some barriers to these goals may be a lack of trained faculty members using ultrasound and insufficient recording mechanisms for residents performing ultrasound procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Ultrasonography is known to be highly operator dependent, and the extent of formal or informal training on its use varies . A recent survey of otolaryngology residents found that 44% reported not feeling comfortable performing ultrasonography-guided procedures, and 43% reported not having performed any as part of their residency training . Formal ultrasonography training is offered by the American College of Surgeons, and a study of physician sonographers found that surgeons who had successfully completed training were more likely to correctly identify cervical lymph node status than nonsurgeon sonographers …”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is known to be highly operator dependent, and the extent of formal or informal training on its use varies . A recent survey of otolaryngology residents found that 44% reported not feeling comfortable performing ultrasonography-guided procedures, and 43% reported not having performed any as part of their residency training . Formal ultrasonography training is offered by the American College of Surgeons, and a study of physician sonographers found that surgeons who had successfully completed training were more likely to correctly identify cervical lymph node status than nonsurgeon sonographers …”
Section: Discussionmentioning
confidence: 99%
“…Learning these skills requires good training and a lot of experience in interventional ultrasound [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided punch biopsy and puncture are cost-effective, accurate, and low-risk methods for this [5,6]. Learning these skills requires good training and a lot of experience in interventional ultrasound [7]. There are many commercially available ultrasound models for training purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Still, only a few countries have incorporated formal ultrasound training into their otolaryngology residency programs 11 . A study from the United States found strong interest in surgeon‐performed ultrasound among 78% of the otolaryngology residents, while only 24% had attended a formal ultrasound course 12 . Hands‐on courses are also associated with considerable monetary cost and faculty time, and transferring skills learned in a simulated setting to clinical practice can be difficult 13 .…”
Section: Introductionmentioning
confidence: 99%